2014
DOI: 10.1136/bjophthalmol-2013-304460
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous venous malformations of the orbit (so-called cavernous haemangioma): a comprehensive evaluation of their clinical, imaging and histologic nature

Abstract: Cavernous haemangioma demonstrate clinical features and growth characteristics of a benign mass. Dynamic imaging highlights their slow flow vascular nature. Histologically, the hypercellularity and stromal changes identified can be understood within the pathogenic context of thrombosis and recanalisation in an organised lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
80
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 39 publications
(44 reference statements)
3
80
0
5
Order By: Relevance
“…The general goal of surgical management is definitive resection because the fate of lesions after partial resection is not well established in the literature. 14 The purpose of this study was to create a composite of the collective global experience on purely endoscopic endonasal resection of OCHs from primary records. By combining the experience of multiple international centers on addressing a single type of pathology, we have been able to generate a moderate series of an otherwise rare procedure.…”
mentioning
confidence: 99%
“…The general goal of surgical management is definitive resection because the fate of lesions after partial resection is not well established in the literature. 14 The purpose of this study was to create a composite of the collective global experience on purely endoscopic endonasal resection of OCHs from primary records. By combining the experience of multiple international centers on addressing a single type of pathology, we have been able to generate a moderate series of an otherwise rare procedure.…”
mentioning
confidence: 99%
“…Similar lesions have been described in a variety of sites including the liver and the skin 1 2. Recently, we have described the clincopathophysiological nature of orbital cavernous malformations 3. The purpose of this follow-up investigation is to extend these findings to lesions of the liver and skin.…”
mentioning
confidence: 93%
“…However, over the past two decades a universal classification system has been developed and propagated 4. Within this system, cavernous lesions are classified as a slow flow venous anomaly 3 5 6…”
mentioning
confidence: 99%
“…No. In a recent research Rootman et al [5] have demonstrated that CHs are noninfiltrating, focal venous malformations. They lack hyperplasia, that is, the cell turnover rate is not altered and they grow (when they do it, by an average 10 % per year) owing to phenomena of localized intravascular coagulation (LIC) and subsequent inflammation [6].…”
mentioning
confidence: 99%